OPTIMALISASI PERAN PENGURUS UKM KEROHANIAN ISLAM DALAM MENUMBUHKAN JIWA RELIGIUS MAHASISWA UNIVERSITAS BHINEKA PGRI - Nisa', Charisma Aulia; Djatmiko, Andreas Andrie; Winarsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The weakening of the internalization of religious values among students due to the influence of modernization, technological development, and pragmatic lifestyles has become a challenge in fostering religious character at universities. The Islamic Spirituality Student Organization (UKM Kerohanian Islam) acts as a venue for religious development through various ongoing religious activities. This study aims to analyze the methods used by the administrators of the Islamic Spirituality Student Organization to nurture the religious spirit of students at Bhineka PGRI University and to identify supporting and inhibiting factors. The study uses a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation. The results show that religious development is carried out through habituation of worship, Islamic studies, religious training, and involving students in various organizational activities. Supporting factors include campus support, availability of facilities, the enthusiasm of administrators, and member cooperation. Meanwhile, the hindering factors include weak communication and coordination, students' limited time, and low consistency in member participation. This study concludes that the Islamic Spiritual Student Organization leaders play an important role in nurturing students' religious spirit, so strengthening organizational management and program innovation is needed to optimize the religious development process.